Research Progress on Coinfection and Activation of Merkel Cell Polyomavirus in HIV/AIDS Patients - Xianfeng ZHOU; Xiaotong QI; Liang LU; Yong AI; Changhua FENG (Zhongliu Fangzhi Yanjiu)
Merkel cell polyomavirus (MCV) was named thus because it is the causative agent of Merkel cell carcinoma (MCC), with 80% of MCC cases being MCV-positive. MCV has been classified as a 2A carcinogen. It promotes carcinogenesis by integrating T antigens into the cell genome. The anti-MCV seroprevalence in the general population is as high as 90%. Usually, MCV is latent after infection in immunocompetent patients, and the incidence of MCC in immunosuppressive or defective patients, such as those with organ transplants, chronic lymphocytic leukemia, and HIV infection, is remarkably high. Patients with HIV/AIDS are a typical population with acquired immunodeficiency. At present, the research on patients with HIV/AIDS and MCV infection, activation, and pathogenesis is limited. In this paper, the progress of previous research is reviewed and the relationship between HIV infection and MCV activation is systematically investigated to provide a reference for the prevention and treatment of MCC in key populations, such as patients with HIV/AIDS.